An Assessment of the Contribution of UK-Funded Projects to the Fight Against Organized Crime and Narcotics: The Case of Ghana Between 2010 to 2020. - Yusif, S. (University of Ghana, 2023)
Many research and public discussions have centred on the significance of aid to country development. Without a doubt, development aid remains an essential aspect of Ghana's development narrative. It is a major financial inflow that helps to buffer Ghana's development. Over the years, the development literature is replete with donor nations' contributions aimed at augmenting developing countries' efforts toward growth and socioeconomic development. This examined the overall contributions of UK aid to Ghana's development, specifically its contributions to the fight against organized crime. The study was guided by the theory of international cooperation which highlights the gains of bilateral and multilateral relationships because of the shred benefit it presents to the actors involved. The study adopted a case study approach, which is qualitative method in the research. According to the study's findings, the United Kingdom was instrumental in the nation’s journey in fighting organized crime. Another finding demonstrated that the UK had contributed immensely to law enforcement agencies in their fight against the menace of organized crime. Another important finding is that the collaboration between the two states led to an improvement in intelligence sharing, logistical support, better training and generally a better service delivery of the Narcotics Control Commission. Aside this contribution to the Narcotics Control Commission, the UK government has also made considerable contributions to the efforts of the Economic and Organized Crime Office. The study however identified some challenges such as the lack of coordination, regional differences, legislation issues, financial challenges, and poor technical and skill capacities as some major factors inhibiting the progress made in combating organized crime. The study recommends the need for government to ensure the provision of financial, logistical and infrastructural resources to enhance and accommodate the operations of law enforcement agencies in the country. The study concludes the UK-Ghana partnership has made some considerable contributions towards the fight against Organized crime within the country.
MA. International Affairs
Keywords: Crime; Narcotics; Ghana